The Role of Teachers in Learning for Children with Special Needs in Elementary Schools - Chevinda Julvianti; Garnish Gemintang Gmaries; Nabila Qonitah Vidyayanti; Zulfadewina (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Inclusive education ensures equal learning opportunities for children with special needs (ABK). This study explores the role of teachers in educating ABK at SDN Baru 06 Pagi, Jakarta. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that ABK at this school exhibits diverse classifications, including ADHD, dyslexia, slow learners, and intellectual disabilities. Teachers implement individualized learning approaches and inclusive strategies to maximize students' potential, emphasizing differentiated instruction and adaptive teaching methods. Additionally, collaboration with parents plays a crucial role in supporting students’ academic and social development. Despite these efforts, several challenges persist, such as limited access to specialized training for teachers and inadequate learning facilities, which hinder the effectiveness of inclusive education. The study underscores the need for continuous professional development programs, government support, and well-equipped learning environments to enhance the quality of education for ABKs. Strengthening teacher competencies and promoting inclusive policies can significantly contribute to fostering an equitable and supportive learning experience. These findings highlight the importance of ongoing improvements in inclusive education practices to ensure that ABK receive the necessary support to reach their full potential.